To All the World : Preaching and the New Evangelization - Connors, Michael E. (Book collections on Project MUSE., 2016)
Pope Francis's vision of the ministry of preaching offers a renewed emphasis on what it means to preach the Word of God in such a way that it transforms lives and communities, and inspires hope. In To All the World, Michael Connors, CSC, draws together contributions from a variety of expert voices to reflect on the importance of liturgical preaching today. To All the World combines contemporary scholarship with pastoral practicality in one volume by well-known practitioners in the ministry of preaching including Timothy Radcliffe, OP, Honora Werner, OP, Paul Turner, Jeremy Driscoll, OSB, Karla J. Bellinger, and Cardinal Donald Wuerl. It will serve as a perfect companion to the United States Bishops' document, Preaching the Mystery of Faith: The Sunday Homily, and will be of interest to all those who share the pope's vision and call to be evangelists of the Word to all the world.